Frequency, Family and Social Aspects of TS - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Results of a prospective, longitudinal study of 21 children recruited at age 2 1/2 to 3 1/2 years without tics but with a first-degree relative with Tourette syndrome (TS) are reported from the Department of Psychology and Child Study Center, Yale University, New Haven, CT.